Photosynthetic characteristics of non‐foliar organs in main C3 cereals. Issue 1 (4th November 2018) - Hu, Ling; Zhang, Yunxiu; Xia, Haiyong; Fan, Shoujin; Song, Jie; Lv, Xuemei; Kong, Lingan
Abstract : Photosynthesis in non‐foliar organs plays an important role in crop growth and productivity, and it has received considerable research attention in recent years. However, compared with the capability of photosynthetic CO2 fixation in leaves, the distinct attributes of photosynthesis in the non‐foliar organs of wheat (a C3 species) are unclear. This review presents a comprehensive examination of the photosynthetic characteristics of non‐foliar organs in wheat. Compared with leaves, non‐foliar organs had a higher capacity to refix respired CO2, higher tolerance to environmental stresses and slower terminal senescence after anthesis. Additionally, whether C4 photosynthetic metabolism exists in the non‐foliar organs of wheat is discussed, as is the advantage of photosynthesis in non‐foliar organs during times of abiotic stress. Introducing the photosynthesis‐related genes of C4 plants into wheat, which are specifically expressed in non‐foliar organs, can be a promising approach for improving wheat productivity.